The values of philippine coastal resources : - White, Alan T. (Coastal Resource Management Project, 1998)
This book has many uses in assisting the way we value our natural resources. It can serve as a reference for finding and citing information required to make informed decisions about when and how to protect and manage coastal resources in the Philippines and elsewhere.